Pulsed electron beam propagation in gases under pressure of 6.6 kPa in drift tube - Kholodnaya G. E. Galina Evgenievna; Sazonov R. V. Roman Vladimirovich; Ponomarev D. V. Denis Vladimirovich; Remnev G. E. Gennady Efimovich; Poloskov A. V. Artem Viktorovich (2016, 2016)
Title screen